Caesarean section rates from Malaysian tertiary hospitals using Robson's 10-group classification - Shamala Devi Karalasingam; Ravichandran Jeganathan; Ravindran Jegasothy; Daniel D. Reidpath (BMC, 2020)
Abstract Background Rising caesarean section rates is a concern worldwide. This study aimed to use Robson's ten group classification to identify which groups of women were contributing most to the rising caesarean section rates in Malaysian tertiary hospitals and to compare between hospitals, using a common standard set of variables. Methods A 5-year (2011-2015) cross-sectional study was conducted using data from the Malaysian National Obstetrics Registry (NOR). A total of 608,747 deliveries were recorded from 11 tertiary state hospitals and 1 tertiary hospital from the Federal territory. Results During the study period, there were 141,257 Caesarean sections (23.2%). Caesarean sections in Group 1 (nulliparous term pregnancy in spontaneous labour) and Group 3 (multiparous term pregnancy in spontaneous labour) had an increasing trend from 2011 to 2015. The group that contributed most to the overall caesarean section rates was Group 5 (multiparous, singleton, cephalic≥37 weeks with previous caesarean section) and the rates remained high during the 5-year study period. Groups 6, 7 and 9 had the highest caesarean section rates but they made the smallest contribution to the overall rates. Conclusions Like many countries, the rate of caesarean section has risen over time, and the rise is driven by caesarean section in low-risk groups. There was an important hospital to hospital variation. The rise in caesarean section rates reflects a globally disturbing trend, and changes in policy and training that creates a uniform standard across hospitals should be considered.